Mobility Gardens within Urban Footpaths and Cycling Itineraries. A Landscape Planning Experience for the Roundabouts System of Imola, Bologna Metropolitan Area, Italy (breakout presentation). (December 2017) - Dall'Ara, Enrica; Maino, Elisabetta; Gatta, Giulia; Torreggiani, Daniele; Tassinari, Patrizia
Abstract : The sprawl of roads networks and the evolution of their typologies have gradually gone creating new types of mobility-related public open spaces which, despite their small individual extension or fragmentation, on the whole could play a significant role in implementing more sustainable built environment, vibrant connections and biodiversity in urban habitats. In particular, considering in an integrated way green spaces along vehicular circulation and walkable pathways, cycling itineraries, urban parks and facilities, can offer opportunities to define a distinctive feature of the city and provide important social and psychological benefits. The work presents a multi-criteria method for a unitary planning and design on green areas along urban road networks, conceiving them as "gardens", to improve both environmental quality and scenic values within circulation systems, and contribute to increase human well-being, urban environment resilience, and imageability of the city. Our methodology has been calibrated through a case-study on public open spaces at roundabouts intersections, in the Imola urban territory, within the Bologna Metropolitan Area (Italy), which include pedestrian or bicycle crossings as well as residual green areas, and are spread in various relevant contexts, i.e. along historical roads, in the main entrances to the City Center, in natural areas near the river, in everyday communities environments, etc. The study addresses a combination of multiple design issues (visual perception, landscape ecology, socio-economic sustainability) and interprets each specific urban context, identifying civic functions (residential, commercial, industrial, cultural, recreational, etc.) and landscape-potential, evaluating also the need for sustainable construction and management solutions. The work proposes a cross-scale approach, defining an overall Masterplan at the urban landscape level, spatial composition criteria for distinctive roundabouts systems, vegetation abacus and maintenance plans, articulated also considering strategic greening categories, such as Wild Flowers areas, Urban Groves, Rain Gardens, Dry Gardens. We hope to provide a useful contribution to the construction of walkable urban places in which for people it is easy to orient and to have comfortable and pleasant experience, so to improve circulation liveability, by means the environmental and aesthetic benefits historically associated to the "garden" concept.